2022
DOI: 10.1159/000524977
|View full text |Cite
|
Sign up to set email alerts
|

Combination Immunotherapy with Anti-PD-1/PD-L1 Antibody plus Anti-VEGF Antibody May Promote Cytotoxic T Lymphocyte Infiltration in Hepatocellular Carcinoma, Including in the Noninflamed Subclass

Abstract: NA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although residual viable tumor within treated nodules may be detected by contrast-enhanced ultrasound, these tumors will become completely undetectable on contrast-enhanced ultrasound after an additional 4–6 cycles of Atezo/Bev. Atezo/Bev after TACE-induced tumor antigen release may enhance immunity by inducing the activation and infiltration of CD8-positive T cells [ 16 , 25 ], which attack residual tumor, resulting in achievement of CR [ 6 , 7 ]. ABC-LEN-TACE sandwich therapy results in cancer-free and drug-free status in most patients (Fig.…”
Section: Indications and Timing For Conversion To Curative Therapymentioning
confidence: 99%
“…Although residual viable tumor within treated nodules may be detected by contrast-enhanced ultrasound, these tumors will become completely undetectable on contrast-enhanced ultrasound after an additional 4–6 cycles of Atezo/Bev. Atezo/Bev after TACE-induced tumor antigen release may enhance immunity by inducing the activation and infiltration of CD8-positive T cells [ 16 , 25 ], which attack residual tumor, resulting in achievement of CR [ 6 , 7 ]. ABC-LEN-TACE sandwich therapy results in cancer-free and drug-free status in most patients (Fig.…”
Section: Indications and Timing For Conversion To Curative Therapymentioning
confidence: 99%
“…More precisely, bevacizumab, with its anti-VEGF activity, can enhance the effect of immune checkpoint inhibitors at almost all 7 steps in the cancer immunity cycle even in HCC with underlying NASH. Particularly, because bevacizumab attacks tumors to promote tumor antigen release and also upregulates ICAM1 and VCAM1 in addition to CXCL9, and thereby facilitates intratumor infiltration of CD8 + T cells [ 21 ], atezolizumab plus bevacizumab combination therapy is likely to be effective even in HCC with underlying NASH.…”
Section: Treatment Effects Of Immune Checkpoint Inhibitors By Etiologymentioning
confidence: 99%
“…Almost all drugs used as first- and second-line systematic therapy have anti-VEGF activity; thus, a lack of response to these drugs might be related to resistance to anti-VEGF therapy. A recent report has shown that anti-VEGF therapy could induce CD8+ T cell infiltration in HCC; therefore, immune checkpoint inhibitors combined with bevacizumab (e.g., atezolizumab and bevacizumab) could achieve a good response [ 25 , 26 , 27 ]. Additionally, interruption of bevacizumab tended to be higher in patients treated with atezolizumab and bevacizumab as third-line or later line systematic therapy, compared with those treated as first or second line ( p = 0.09).…”
Section: Discussionmentioning
confidence: 99%